Small carrion beetles (Coleoptera: Leiodidae: Cholevinae) from caves in Iran, with additional taxonomical notes on Anemadus sengleti and Catops farsicus - Tahami, Mohadeseh Sadat; Růžička, Jan; Sadeghi, Saber; Jakubec, Pavel; Novák, Martin (Zootaxa, 2017)
Distributional data on Cholevinae found in caves in Iran are presented. In total, three species are reported. Anemadus sengleti Giachino & Vailati, 1993 is redescribed, including previously unknown female characters, based on material from two localities in Iran, with the first records from Isfahan, and Kohgiluyeh and Boyer-Ahmad Provinces. Catops farsicus Giachino & Vailati, 2000 is redescribed, including the previously unknown male characters, based on material from eight localities in Iran, with the first records from Chaharmahal and Bakhtiari, Isfahan and Kohgiluyeh and Boyer-Ahmad Provinces. The distribution of both species is mapped. The widely distributed Cholevinus pallidus pallidus (Ménétries, 1832) is reported for the first time from Isfahan and North Khorasan Provinces.